Early earnings trajectories of international students after graduation from postsecondary programs - Feng Hou; Youjin Choi; Ping Ching Winnie Chan (Economic and Social Reports)
There is considerable global competition for international students, who are often seen as strong candidates for economic immigration to countries that are facing current and future skills and labour shortages. International students bring extensive economic and social benefits to the host country. This study compares the earnings of international students with those of domestic students during their first five years after graduation from Canadian postsecondary institutions, and investigates the role of various pre-graduation characteristics in accounting for their earnings differences. This study also examines how the trajectories of earnings gaps vary between international and domestic graduates, across levels of education and major fields of study.